A Comparison of the Degree of Student Satisfaction using a Simulation or a Traditional Wet Lab to Teach Physical Properties of Ice. Issue 1 (January 2015) - Crandall, Philip G.; O'Bryan, Corliss A.; Killian, Susan A.; Beck, Dennis E.; Jarvis, Nathan; Clausen, Ed
Abstract It is often difficult to offer food chemistry students traditional, hands‐on laboratory experiences due to lack of funds for equipment, insufficient laboratory space, or the nature of distance education. A traditional wet laboratory exercise was developed to demonstrate the effects of the physical properties of ice formation when making high‐quality sorbets, varying the amounts of sugar, water, and stabilizer. This wet lab was compared to a simulated, detective‐based crime scene investigation (CSI) of why a famous food scientist's sorbet had become a "stiff." Forty‐six food chemistry students were randomly assigned to groups, completing either the traditional wet lab or the simulated lab 1st before completing the 2nd type of laboratory. While there were preferences for one lab over another, there were no differences in the learning outcomes between the 2 laboratory formats. Students who preferred the simulated lab felt they could move at their own pace and were able to stop and review the simulation to understand the concepts more clearly. Traditional wet lab proponents liked working in groups and having immediate access to instructors. From the initial evaluation it appears that simulations could be used as replacements for hands‐on laboratory experiences or could serve as effective introductions to laboratory principles and concepts, resulting in increased student learning.